2011
DOI: 10.3746/jfn.2011.16.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phytochemical Contents and Biological Activities from the Fruits of Elaeagnus multiflora

Abstract: The purpose of this study was to investigate the phytochemical contents and biological activities, including α-glucosidase inhibitory activity and antioxidant activity, from the fruits of Elaeagnus multiflora using different solvent systems. The 50% ethanol extract of this species showed the most potent α-glucosidase inibitory activity (88.5%) at a concentration of 1 mg/mL. Moreover, this extract also displayed the strongest antioxidant activity in each assay, showing 96.3% in DPPH scavenging activity, 98.2% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Additionally, many species are commonly used in traditional medicine to treat symptoms such as cough, diarrhea, itching and foul sores. Phytochemical studies have shown various medicinal properties of this genus, including antioxidant and anti-tumor (Kim et al, 2007;Lee and Seo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many species are commonly used in traditional medicine to treat symptoms such as cough, diarrhea, itching and foul sores. Phytochemical studies have shown various medicinal properties of this genus, including antioxidant and anti-tumor (Kim et al, 2007;Lee and Seo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This carotenoid is responsible for their red color and has been extensively studied as one of the major dietary carotenoids for humans [2]. Lee et al [3] demonstrated that in addition to chlorophylls, the leaves of cherry silverberry have high contents of sugars, fatty acids, and phytosterols. However, the polyphenolic profile of cherry silverberry fruits has not yet been thoroughly recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The genus was considered invasive in many parts of the world until the nutritional and medicinal properties of several species have been explored in the past years (Patel, 2015). In particular, the species Elaeagnus multiflora Thunb., also known as cherry silverberry (CS), has been investigated for the phytochemical content (Lee, Seo, & Cho, 2011); antioxidant and antiproliferative activities (Oh & Lee, 2008); anti-inflammatory and whitening effects (Lee et al, 2007); and anticancer properties (Lee, Lee, & Park, 2010) of its different solvent extracts. Because of the fruit's promising potential as a functional food, it is important to apply processing techniques that would not only lengthen its shelf-life, but also enhance its biological activities.…”
Section: Introductionmentioning
confidence: 99%